AI in Vocational English Classrooms: Mapping Teachers’ Knowledge, Benefits, and Pedagogical Uses - Radita, Cindy; Yuniar, Rendhi Fatrisna (Proceeding of International Conference on Islamic Education (ICIED), 2025)
The rapid progress of educational technology has caused big changes in English for Specific Purposes (ESP) instruction, especially in vocational education. Among these innovations, Artificial Intelligence (AI) has become a revolutionary tool that is changing the way teachers design lessons, assess learning, and engage students. Although AI has the potential to create adaptive and engaging learning environments, the ways in which vocational English teachers apply these tools to ESP instruction remains largely unexplored. The present study addresses the gap in research on vocational English teachers’ familiarity with AI tools, their perceived benefits, and the challenges they encounter when integrating these tools into ESP instruction. This study draws on qualitative data obtained through surveys and semi-structured interviews involving vocational English teachers in Malang, Indonesia. The thematic analysis was used to analysis and interpret teachers’ attitudes and experiences in leveraging AI tools in the classroom. The findings reveal varying levels of familiarity with AI, categorized as low, middle, or high, indicating different perceptions and practices of integrating AI into ESP instruction. Additionally, the findings indicate that teachers recognize AI’s contributions to enhancing student engagement, supporting personalized learning, and improving lesson efficiency. However, teachers also reported challenges, particularly regarding readiness, the need for continuous professional development, and maintaining a balanced relationship between technology use and human interaction. The study underscores the importance of teacher training and institutional support to ensure that AI serves as a complementary tool that enhances, rather than replaces, the human dimension of vocational language teaching. By offering empirical evidence from a vocational ESP context which is a setting rarely explored in existing AI literature, the study extends understanding and offers practical implications for sustainable AI integration in language education.